2018
DOI: 10.1007/s11356-018-1409-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbial communities to red mud-based stabilizer remediation of cadmium-contaminated farmland

Abstract: In this work, a field test was conducted to investigate the effects of heavy metal stabilizer addition on brown rice and microbial variables in a cadmium (Cd)-contaminated farmland from April to October in 2016. Compared with the control, red mud-based stabilizer (RMDL) effectively reduced the concentration of Cd in brown rice (with the removal rate of 48.14% in early rice, 20.24 and 47.62% in late rice). The results showed that adding 0.3 kg m RDML in early rice soil or soil for both early and late rice incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The combined application of IMOs and n-HAP exhibited synergistically decreased DTPA-extractable Cd and Pb concentrations in slightly contaminated soil; however, no synergistic effect was observed in moderately contaminated soil. Some studies have revealed that stabilising amendments in the heavy-metal-polluted soil aided the recovery of soil bacterial diversity and soil microbial metabolic activities related to Cd and Pb transformation and enriched genera related to nutrient activation, particularly at low metal concentrations [ 68 , 69 , 70 , 71 ]. Our results suggest that n-HAP, along with several taxa, may improve the immobilisation efficiencies of DTPA-extractable Cd and Pb in slightly contaminated soil, whereas IMOs from moderately contaminated soil developed many strains tolerant to HMs, thereby activating the available Cd in moderately contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…The combined application of IMOs and n-HAP exhibited synergistically decreased DTPA-extractable Cd and Pb concentrations in slightly contaminated soil; however, no synergistic effect was observed in moderately contaminated soil. Some studies have revealed that stabilising amendments in the heavy-metal-polluted soil aided the recovery of soil bacterial diversity and soil microbial metabolic activities related to Cd and Pb transformation and enriched genera related to nutrient activation, particularly at low metal concentrations [ 68 , 69 , 70 , 71 ]. Our results suggest that n-HAP, along with several taxa, may improve the immobilisation efficiencies of DTPA-extractable Cd and Pb in slightly contaminated soil, whereas IMOs from moderately contaminated soil developed many strains tolerant to HMs, thereby activating the available Cd in moderately contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Organic stabilizers such as animal manure, crop residues, sewage sludge, and industrial organic waste also can inert and remediate heavy metals. Red mud-based stabilizers and montmorillonite-biochar composite materials have been used to remediate pollutants effectively [15] .…”
Section: Chemical Remediation Of Agricultural Soilsmentioning
confidence: 99%
“…Due to environmental issues and the high cost associated with managing and disposing of it, there is a growing concern about the proper disposal of this waste. Alternative uses of BR have been studied in the ceramics industry [4], stabilizer soil [5] and metal recovery, among others [2]. However, there are some limitations, such as excess in moisture, hazardous rating of bauxite residue, viable logistics in the transport of waste and the low aggregate value in BR.…”
Section: Introductionmentioning
confidence: 99%